Gender Identity, Ethnic Identity, and Smoking among First Nations Adolescents - Greaves, Lorraine; Johnson, Joy; Qu, Annie; Okoli, Chizimuzo T.C.; Hemsing, Natalie; Barney, Lucy (UKnowledge, 2012)
Smoking rates among Aboriginal adolescents are the highest of any population group in British Columbia, Canada. Recent studies suggest that substance use is affected by gender and ethnic identity among youth. The purpose of our study was to explore the association of gender and ethnic identity with smoking behaviour among First Nations adolescents. This study is based on a convenience sample (i.e., an on-hand, readily available sample) of 124 youth (123 First Nations and 1 Métis) recruited at youth drop-in centres, health fairs, and cultural activities. We obtained information on demographics, smoking history, Bem Sex Role Inventory (BSRI), composite measure of gender and gender identification (GID), and Moran’s Bicultural Ethnic Identity Questionnaire (Bicultural ID). We examined the associations between gender role identification and cultural identification on current smoking status among First Nations youth by using logistic regression analyses stratified by gender. In stratified multivariate regression analysis among girls, current smoking was significantly associated with lower scores on the aggressive masculinity index of the Gender ID scale and the White/Canadian index of the Bicultural ID scale. Among boys, current smoking was significantly associated with higher scores on the affective femininity index of the Gender ID scale and lower scores on the White/Canadian index of the Bicultural ID scale. Reducing smoking among First Nations groups remains an important priority for tobacco control in Canada. Understanding the gendered and cultural aspects of smoking may be instrumental in improving prevention and cessation efforts among First Nations youth.